2017
DOI: 10.1001/jamainternmed.2016.9662
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Primary Care Access Between 2012 and 2016 for New Patients With Medicaid and Private Coverage

Abstract: Of note, this study considers only new patients calling in-network offices. We cannot measure access for established patients nor can we control for the myriad health system changes that occurred during the same period. While the 10 states were selected for diversity along a number of dimensions, our results may not be generalizable to other settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 3 publications
(6 reference statements)
4
41
0
Order By: Relevance
“…This finding is consistent with prior research that shows that primary care appointment availability increased and short wait times decreased for Medicaid patients from 2012–2016. 21 Further, our findings are consistent with prior research that studied coverage and access to care during the first two years of ACA Medicaid expansion which showed that there were significant reductions in cost-related barriers to care in 2015, the second year of ACA implementation. 22 Our results are consistent with a recent study in Northern California that showed that Medicaid enrollees were more likely to use smoking cessation treatment, relative to smokers enrolled in nonexchange commercial plans.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with prior research that shows that primary care appointment availability increased and short wait times decreased for Medicaid patients from 2012–2016. 21 Further, our findings are consistent with prior research that studied coverage and access to care during the first two years of ACA Medicaid expansion which showed that there were significant reductions in cost-related barriers to care in 2015, the second year of ACA implementation. 22 Our results are consistent with a recent study in Northern California that showed that Medicaid enrollees were more likely to use smoking cessation treatment, relative to smokers enrolled in nonexchange commercial plans.…”
Section: Discussionsupporting
confidence: 90%
“…23 Polsky et al found early evidence that increased Medicaid reimbursement to primary care providers, as mandated in the ACA, was associated with improved appointment availability for Medicaid enrollees among participating providers, without generating longer waiting times, 24 and later found appointment availability persisted despite the end of the Medicaid primary rate increase. 25 The increase in new patients without an impact on same or next-day appointments is similar to results from the Kaiser Family Foundation survey assessing PCP experiences with, and attitudes about, Medicaid expansion that found a lack of perceived impact on quality of care or patient satisfaction. 26 According to PCPs, while access to care improved greatly for previously uninsured patients, access to some services (e.g., specialty care, mental health care) sometimes remained challenging for enrollees and their PCPs, and lagged behind reported access for those with private insurance.…”
Section: Discussionsupporting
confidence: 69%
“…While we hypothesized that access to care would remain stable or improve with the additional funding that was available under the ACA, we recognized that CHCs may instead have decreased their acceptance of certain patient groups or increased wait times for appointments in the face of greater demand. In a recent study using data from the same 2012/2013 audit and a similar audit conducted in 2016, we found that overall new patient appointment availability has increased for patients with Medicaid and has remained stable for those with employer‐sponsored insurance, while wait times for appointments slightly increased across both groups . That study did not separately compare changes in appointments at CHCs with those at non‐CHC physician offices.…”
Section: Introductionmentioning
confidence: 83%
“…In a recent study using data from the same 2012/2013 audit and a similar audit conducted in 2016, we found that overall new patient appointment availability has increased for patients with Medicaid and has remained stable for those with employer-sponsored insurance, while wait times for appointments slightly increased across both groups. 7 That study did not separately compare changes in appointments at CHCs with those at non-CHC physician offices. Accordingly, we examine changes at CHCs in appointment availability and wait times from 2012/2013 to 2016 and compare these data to changes for non-CHC physician offices.…”
Section: Introductionmentioning
confidence: 99%